2021
DOI: 10.21203/rs.3.rs-32594/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health literacy and health outcomes in China’s floating population: mediating effects of health services

Abstract: Background: The floating population in China consists primarily of internal immigrants and represents a typical health vulnerable group. Poor health literacy has recently become an obstacle in the accessibility and utilization of health services for the vulnerable population, leading to adverse health outcomes. This study aimed to examine whether health literacy affected health outcomes in China’s floating population and whether health service utilization had a mediating effect between health literacy and heal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…First, we estimated the model without controlling for any variables. The regression results shown in Column (1) indicate that females have lower health insurance coverage than males, and the differences in health insurance coverage between females and males increase with age. Next, in Column (2), we controlled for city-fixed effects, and the key coefficients did not significantly change in magnitude or significance level compared to Column (1).…”
Section: Gender Differences In Medical Insurance Participation Rate O...mentioning
confidence: 98%
See 2 more Smart Citations
“…First, we estimated the model without controlling for any variables. The regression results shown in Column (1) indicate that females have lower health insurance coverage than males, and the differences in health insurance coverage between females and males increase with age. Next, in Column (2), we controlled for city-fixed effects, and the key coefficients did not significantly change in magnitude or significance level compared to Column (1).…”
Section: Gender Differences In Medical Insurance Participation Rate O...mentioning
confidence: 98%
“…The regression results shown in Column (1) indicate that females have lower health insurance coverage than males, and the differences in health insurance coverage between females and males increase with age. Next, in Column (2), we controlled for city-fixed effects, and the key coefficients did not significantly change in magnitude or significance level compared to Column (1). Finally, when we controlled for related variables in Column (3), we found that although the coverage of health insurance for migrant workers tends to rise with age, this trend is influenced by gender, with less of an increase for females than males.…”
Section: Gender Differences In Medical Insurance Participation Rate O...mentioning
confidence: 98%
See 1 more Smart Citation
“…Population migration has drawn increasing scholarly interest and relevant studies mainly focus on settlement intention ( 2 , 3 ), income level ( 4 ), health ( 5 ), social integration ( 6 ), and other aspects of the migrants. The population migration often exhibits three patterns: settling in inflow region, continuous migration and return migration.…”
Section: Introductionmentioning
confidence: 99%